ACS Earth and Space Chemistry - ACS Earth and Space Chemistry (American Chemical Society, 2026)
ACS Earth and Space Chemistry advances interdisciplinary application of chemistry to natural materials and processes in Earth's interior, surface, and atmosphere, and in space.
FI 0.7
Q2
Keywords: Earth; Space & Environmental Sciences; Acuerdos transformativos; Geochemistry & Mineralogy; Transformative agreements; Química de materiales y procesos naturales; Química de superficies; Química de la atmósfera terrestre